A high-efficiency pretreatment method for elution of pathogenic bacteria in lettuce. (19th October 2022) - Liao, Xiaoyan; Pu, Chunmin; Cui, Yan; Bai, Yalong; Shi, Xianming; Chen, Lili
Abstract: Many current studies on rapid detection of pathogenic bacteria in foods have focused on the construction of detection methods, neglecting pretreatment. It is also a key step to efficiently elute pathogenic bacteria from food samples for rapid detection and can even determine the success or failure of an assay. In this study, we used Escherichia coli ( E. coli ), Salmonella enteritidis ( S. enteritidis ), and Listeria monocytogenes ( L. monocytogenes ) as model bacteria to compare the elution efficiency of different eluants; explore the effect of surfactant, ionic strength, protein (or amino acid and peptide), and enzyme on the recovery rate of bacteria in lettuce; and compare the compound effect caused by multiple factors. Finally, we developed an efficient bacterial recovery method and confirmed the superiority of this method to analyze the bacterial diversity of eluants from lettuce. The results showed that the recovery efficiency of E. coli, S. enteritidis, and L. monocytogenes, which were artificially contaminated with approximately 10 5 CFU/g in lettuces, could reach 94.4%, 90.6%, and 93.7% by using 10 mmol/L Tris·HCl (pH 9.5) with 0.1% peptone and 300 U/100 mL of cellulase, and furthermore, the elution efficiency could reach 99.6%, 98.6%, and 100% with the aid of a 2-min stomaching. For the lettuce samples with only native bacteria, the recovery rate reached 92.1% for viable aerobic bacteria by this method, which was approximately 10% higher than that of the modified previous method. The bacterial diversity of the eluted solution was analyzed, and the result was significantly improved. Considering these advantages, it is important to improve the elution efficiency to achieve rapid and accurate detection of pathogenic bacteria in lettuces.